RELEVANSI PENDEKATAN FILOSOFIS DALAM PENGEMBANGAN STUDI ISLAM KONTEMPORER - Haqiah, Nur Azizatul; Aufa Fatchia Rahma; Winda Islamitha Nurhamidah; Rofiatus Sa'adah; Ahmad Arifi (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
This study examines the relevance of the philosophical approach in the development of contemporary Islamic studies. The rapid transformation of Islamic sciences in the modern era demands an analytical framework that is more reflective and critical, particularly when responding to social dynamics, plurality of thought, and technological advancement. Employing a library research method, this paper explores the epistemological foundations, conceptual scope, and contributions of the philosophical approach by analyzing classical and contemporary literature. The findings indicate that the philosophical approach plays a significant role in broadening the horizons of religious interpretation, strengthening methodological reasoning, and fostering critical awareness in understanding both texts and social realities. Philosophy functions not only as a tool for critique but also as a constructive foundation for formulating an integrative and responsive paradigm of Islamic scholarship, especially in addressing modern issues such as radicalism, gender equality, technological ethics, and global humanitarian challenges. Nevertheless, the use of philosophical approaches still encounters several obstacles, including the tendency toward abstract rationality, limited operational application in fiqh, and resistance from normative-textual traditions. This study affirms that repositioning the philosophical approach in a proportional manner is a methodological necessity for strengthening Islamic studies in the contemporary era.